Impact of training volume settings between unilateral training and bilateral training on athletic performance: A systematic review and meta-analysis - Meiling Tao; George P. Nassis; Yuou Song; Mingyue Yin; Chenwen Zhu; Mengde Lyu; Zhili Chen; Yuming Zhong; Chris Bishop; Yongming Li (Journal of Exercise Science & Fitness, 2025)
Background: The unilateral/bilateral dimension refers to whether an action is performed by one side of the body alone or involves both sides simultaneously. Unilateral training (UT) and bilateral training (BT) have been shown to enhance athletic performance. However, there are differences in training volume settings between unilateral and bilateral training, making it essential to understand their characteristics for optimizing training protocols and improving competitive level. Objective: This systematic review aimed to: 1) explore the effects of training volume settings between unilateral training and bilateral training on improvements in athletic performance (muscle strength, jump performance, sprint time, and change of direction time), and 2) investigate the moderating effects on testing metrics, training frequency, and training protocol on athletic performance. Methods: Searches were conducted in PubMed, Medline, Cochrane Library, EBSCOhost, and Web of Science (Core Collection) on June 5, 2024, and updated on April 17, 2025. Included studies were randomized controlled trials that investigated the effects of UT versus BT on athletic performance in athlete. Pooled effects for each outcome were summarized using Standardized Mean Difference [Hedges' g (g)] through a three-level meta-analysis model, and subgroup analyses were used to explore moderators. The certainty of evidence was assessed using the GRADE approach. Results: A total of nine high-quality randomized controlled trials were included, involving 225 athletes. The results showed that there was no significant difference in improving athletic performance whether the training volume of UT and BT was the same (g = 0.20 [-1.56, 1.15], I2-2 = 77.8 %; I2-3 = 0.0 %, low GRADE) or when the UT volume was twice that of BT (−0.04 [-0.14, 0.06], I2-2 = 93.8 %; I2-3 = 0.0 %, moderate GRADE). When the training volumes of UT and BT were the same, the impact on athletic performance was not significantly moderated by test items, training frequency, or training protocols. Neither unilateral test metrics (g = −0.84) nor bilateral test metrics (g = −0.90) showed significant improvement. There was no significant difference between training twice a week (g = −0.16) and training three times a week (g = −0.19). Similarly, there was no significant difference between conducting plyometric training (g = −0.16) and another instance of plyometric training (g = −0.19). When the UT volume was twice that of BT, it might be significantly moderated by test items, but training frequency and training protocols were likely not significant moderators. Unilateral test metrics (g = −0.39) and bilateral test metrics (g = 0.64) both showed significant improvements. There was still no significant difference between training twice a week (g = −0.14) and training three times a week (g = 0.13). Furthermore, there was no significant difference between conducting plyometric training (g = −0.01) and another instance of plyometric training (g = −0.21). Conclusion: The training volume settings between unilateral and bilateral training may not have a significant impact on athletic performance. The testing metrics might be the significant moderating factors, whereas training frequency and training protocol are likely not significant moderators. Prospero registration: CRD42024545511.